Public crime, private justice : the tale of how one of South Africa’s top private investigators gets impressive results and what lessons the men and women of the public police force and the SAPS as an institution might learn from this - Sudheim, Alexander (Centre for Film and Media Studies, 2015)
The role of the police is a fundamental one in any society and in South Africa this role is beset with a unique set of challenges which are organisational, institutional, operational, individual and political in nature. It is these I address by means of examining the South African Police Service from the perspective of the praxis, process, means and methods of a working private investigator in contemporary South Africa. My method in this undertaking is a journalistic one in which I use the narrative techniques of dialogue, description, pacing and reflection to bring to life the stories and characters of police officers; ex-police officers; private investigators; victims of crime and perpetrators of crime in order to bring to light some of the more pressing issues with regard to crime and its prevention in contemporary South African society. This lends drama and suspense to a non-fiction narrative and also involves the reader in such a way that they respond to and engage with the subject matter on a personal level, thereby evoking their own thoughts and feelings on the spectre of crime in South Africa and what the SAPS variously is, isn’t or could be doing about it.